Accurate modeling of nonideal low-power PWM DC-DC converters operating in CCM and DCM using enhanced circuit-averaging techniques - Tannir, Dani (2016)
The development of enhanced modeling techniques for the simulation of switched-mode Pulse Width Modulated (PWM) DC-DC power converters using circuit averaging is the main focus of this article. The circuit-averaging technique has traditionally been used to model the behavior of PWM DC-DC converters without considering important nonideal characteristics of the switching devices. As a result, most of these existing approaches present simplified models that are ideal or linearized, and do not accurately account for the performance characteristics of the converter. This is especially problematic for low-power applications. In this article, we present an enhanced nonideal behavioral circuit-averaged model that makes the simulation of DC-DC converters both computationally efficient and accurate, thereby presenting an important tool for circuit designers. Experimentally, we show that our Verilog-A-based new model allows for accurate simulation of both Buck- and Boost-type PWM converters operating in either CCM or DCM modes while providing more than one order of magnitude speedup over the transistor-level simulation.